Model Basic Clinical Integration from the Interdisciplinarity in the Basic Biomedical Sciences - Arturo Prudencio Puga García; Eduardo Veloso Pérez; Vicente Fardales Macías; Emelina Amiris Llano Gil; Gloria María Puga Madiedo (Gaceta Médica Espirituana)
Background: The basic clinical integration in the teaching-learning of Basic Biomedical Sciences in Medicine careers has directed the training processes based on pedagogical paradigms that have as central focus the meaningful and social constructivist learning.